DESAIN PRIMER GEN EDNRB EKSON 6 DAN OPTIMASI PCR UNTUK ANALISIS MUTASI GEN PADA HIRSCHSPRUNG’S DISEASE - Yuda Meisya, Divia; Ahda, Yuni (Jurnal Biogenerasi, 2025)
Hirschsprung’s Disease (HSCR) is a congenital disorder characterized by the absence of ganglion cells in the intestinal wall, leading to impaired intestinal motility. One of the key genes involved in the pathogenesis of HSCR is the Endothelin Receptor Type B (EDNRB) gene, particularly mutations in exon 6. Detecting these mutations requires specific primers and well-optimized PCR conditions. This study aims to design specific primers for exon 6 of the EDNRB gene using in silico methods and to determine optimal PCR conditions through annealing temperature and primer concentration optimization. Primers were designed based on the EDNRB gene sequence (Accession No. NG_011630.3) using Geneious Prime and validated for specificity using Primer-BLAST. PCR optimization was conducted in vitro using various annealing temperatures 52.8–55.3°C and primer concentrations 0.5–1.1 µM on normal human DNA samples. PCR products were analyzed by 1.5% agarose gel electrophoresis. The primer design for exon 6 of the EDNRB gene yielded the following results: both forward and reverse primers were 20 bp in length, with melting temperatures (Tm) of 58.1°C and 56.1°C, and GC contents of 55% and 50%, respectively. In silico analysis confirmed primer specificity to chromosome 13. Optimal PCR conditions were achieved at an annealing temperature of 55.3°C and a primer concentration of 0.7 µM, yielding a single amplicon of 517 bp.